Pengaruh Peran dan Karakteristik Kepemimpinan Terhadap Sistem Birokrasi Pada Pemerintah Kabupaten Minahasa Utara - Laoh, Sinjo James (JBE (Journal of Business and Economics); Volume 11 No.1, 2012 JBE UNKLAB, 2012)
This research aims to investigate the impact of the government executive role and leadership characteristics toward the bureaucratic system of the local government.  This research used the purposive sampling, and the data was collected through a questionnaire with a sample of 54 respondents.  The findings show that: (1) based on gender, the leadership role did not have a significant effect on the bureaucratic system, (2) based on the latest degree of education, the leadership role and leadership characteristics did not have a significant effect, (3) based on simple regression, the leadership role and the leadership characteristics had significant effect on the bureaucratic system, and (4) based on multiple regressions, both the leadership role and the leadership characteristics had significant effect.